A proposal of a digital learning object for the teaching of sound waves (Research, Society and Development, 2019)
This article aims to present a proposal of development of a Digital Learning Object (DLO) about sound waves, more specifically about the behavior of these waves according to the fundamental wave equation. The idea is that this DLO will be developed and used with high school students or students of the latter years of elementary school. The features of the object, the planning and the aims that we intend to achieve with it will be presented in this work and meet the requirements pointed out by the literature to the development of a Learning Object. A literature review allowed us to conclude that there are not many works related to the DLO that contemplate the issue addressed here. Therefore, we indicate the need of its development so that it can contribute to the improvement of the teaching-learning process.